For all audiences : Incorporating immature stages into standardised spider inventories has a major impact on the assessment of biodiversity patterns - Domènech, Marc (2022)
Although arthropods are the largest component of animal diversity, they are traditionally underrepresented in biological inventories and monitoring programmes. However, no biodiversity assessment can be considered informative without including them. Arthropod immature stages are often discarded during sorting, despite frequently representing more than half of the collected individuals. To date, little effort has been devoted to characterising the impact of discarding nonadult specimens on our diversity estimates. Here, we used a metabarcoding approach to analyse spiders from oak forests in the Iberian Peninsula, to assess (1) the contribution of juvenile stages to local diversity estimates, and (2) their effect on the diversity patterns (compositional differences) across assemblages. We further investigated the ability of metabarcoding to inform on abundance. We obtained 363 and 331 species as adults and juveniles, respectively. Including the species represented only by juveniles increased the species richness of the whole sampling in 35% with respect to those identified from adults. Differences in composition between assemblages were greatly reduced when immature stages were considered, especially across latitudes, possibly due to phenological differences. Moreover, our results revealed that metabarcoding data are to a certain extent quantitative, but some sort of taxonomic conversion factor may be necessary to provide accurate informative estimates. Although our findings do not question the relevance of the information provided by adult-based inventories, they also reveal that juveniles provide a novel and relevant layer of knowledge that, especially in areas with marked seasonality, may influence our interpretations, providing more accurate information from standardised biological inventories.